Історіографія та усна народна хроніка - Златкович, Б. (Народна творчість та етнологія, 2012)
The article deals with the verbal and written materials about the liberation of Serbia in the XIXth century that contribute to cultivating and analyzing the presence and specific transposition of the historical facts against a background of scientific historiography, folk epic, and verbal folk anecdotes.